Cyclin G2 regulates canonical Wnt signalling via interaction with Dapper1 to attenuate tubulointerstitial fibrosis in diabetic nephropathy. Issue 5 (24th January 2020) - Zhao, Chenyang; Gao, Jinlan; Li, Sen; Liu, Qi; Hou, Xiaoyu; Xing, Xuesha; Wang, Danning; Sun, Manni; Wang, Shusen; Luo, Yang
Abstract: Cyclin G2 ( CCNG2 ) is an atypical cyclin that inhibits cell cycle progression and is often dysregulated in human cancers. Cyclin G2 in the occurrence and development of diabetic nephropathy (DN), one of the most severe diabetic complications, has not been fully identified. In this study, we investigated the function and regulatory mechanism of cyclin G2 in DN. In vivo studies revealed that a deficiency of cyclin G2 significantly increased albuminuria and promoted tubulointerstitial fibrosis in established DN. Cyclin G2 regulated the expression of fibrosis‐related proteins via the canonical Wnt signalling pathway in renal tubular epithelial cells. Moreover, the binding of cyclin G2 to Dapper1 (Dpr1/DACT1), a protein involved in Wnt signalling, decreased the phosphorylation of Dpr1 at Ser762 by casein kinase 1 (CK1) and suppressed the Wnt signalling pathway. These findings reveal that cyclin G2 can protect against renal injury and fibrosis associated with DN and, thus, is a new target for the prevention and treatment of diabetic complications.